2017
DOI: 10.1371/journal.pone.0174445
|View full text |Cite
|
Sign up to set email alerts
|

Study on the biodegradation of crude oil by free and immobilized bacterial consortium in marine environment

Abstract: Five strains of bacteria, namely, Exiguobacterium sp. ASW-1, Pseudomonas aeruginosa strain ASW-2, Alcaligenes sp. ASW-3, Alcaligenes sp. ASS-1, and Bacillus sp. ASS-2, were isolated from the Zhejiang coast in China. The mixed flora of the five strains performed well with degrading 75.1% crude oil (1%, w/v) in 7 days. The calcium alginate—activated carbon embedding carrier was used to immobilize bacterial consortium. Immobilized cells performed better than free ones in variations of environmental factors contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 37 publications
4
61
1
Order By: Relevance
“…There was 51.9% crude oil (2% v/v) degradation after 7 days of incubation according to Adam [51]. A study by Chen et al [52] showed about 68% of biodegradation efficiency of crude oil (2% v/v) after 1 week of cultivation. Diesel degradation abilities by Staphylococcus sp., Pseudomonas sp.…”
Section: Biological Removal Of Crude Oil Using Single and Bacterial Cmentioning
confidence: 97%
“…There was 51.9% crude oil (2% v/v) degradation after 7 days of incubation according to Adam [51]. A study by Chen et al [52] showed about 68% of biodegradation efficiency of crude oil (2% v/v) after 1 week of cultivation. Diesel degradation abilities by Staphylococcus sp., Pseudomonas sp.…”
Section: Biological Removal Of Crude Oil Using Single and Bacterial Cmentioning
confidence: 97%
“…Also Al-Wasify and Hamed (2014) obtained 77.8% of crude oil degradation by using Pseudomonas auroginosa after 28 days at 30ºC. Chen et al, (2017) found that optimum temperature for oil degradation with free and immobilized cells of Pseudomonas auroginosa ASW-2 was 30ºC.…”
Section: Effect Of Temperature On Oil Biodegradationmentioning
confidence: 97%
“…The observed differences in the influence of variables and removal efficiencies between the 2-compartment and 3-compartment cells could be related to differences in the EDR process in the two designs. Acidification occurs faster in the 2-compartment cell, resulting in lower pH levels, that in turn may retard the natural bioremediation of oil in the soil [32]. This may also indicate that the observed removal of THC from the soil is related to degradation rather than solubilisation into the liquid phase.…”
Section: -Compartment Cellmentioning
confidence: 99%